2013
DOI: 10.1093/annonc/mdt253
|View full text |Cite
|
Sign up to set email alerts
|

Primary tumor location and bevacizumab effectiveness in patients with metastatic colorectal cancer

Abstract: NCT00212615.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
65
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(74 citation statements)
references
References 20 publications
8
65
0
1
Order By: Relevance
“…22 The current study, which was based on resected CCLM, confirmed that the pathologic response to preoperative chemotherapy, which had previously been demonstrated to be associated with survival, 12 also differed according to embryonic origin.…”
Section: Discussionsupporting
confidence: 82%
“…22 The current study, which was based on resected CCLM, confirmed that the pathologic response to preoperative chemotherapy, which had previously been demonstrated to be associated with survival, 12 also differed according to embryonic origin.…”
Section: Discussionsupporting
confidence: 82%
“…Proximal colonic location outside of the context of MSI-High CRC is associated with greater mortality, especially among stage IV CRC patients (16, 3133). Recent evidence has also documented a poorer response to treatment in patients with proximal CRC (20). …”
Section: Discussionmentioning
confidence: 99%
“…One of the reasons for the poorer survival in AAs compared to EAs may be due to the higher prevalence of proximal neoplasia in AAs (10–15), which is often associated with worse survival (1619), especially in the context of metastatic disease. A recent investigation has found that treatment with biologic agents appears to be less effective in patients with proximal CRC compared to distal or rectal cancer (20). …”
Section: Introductionmentioning
confidence: 99%
“…Antiangiogenic therapy could improve patient survival from advanced colon cancer, in which the benefit differs by tumor location. Boisen et al [18] analyzed the data of metastatic CRC patients who received CapeOX +/bevacizumab as standard first-line therapy. Patients treated with CapeOX + bevacizumab with primary tumors located in the sigmoid colon and rectum had a significantly better outcome than patients with primary tumors located anywhere between the cecum to the descending colon, with results showing PFS (9.3 vs 7.2 mo, HR = 0.68) and OS (23.5 vs 13.0 mo, HR = 0.47).…”
Section: Anti-angiogenic Therapymentioning
confidence: 99%